Editorial - Christian Gütl (Journal of Universal Computer Science)
Dear Readers,It gives me great pleasure to announce the seventh regular issue of 2025. In this issue, 4 papers by 12 authors from 6 countries – Colombia, India, Lithuania, Romania, Spain, Turkiye – cover various topical and novel aspects of computer science. As always, I would like to thank all the authors for their sound research and the editorial board and guest reviewers for their extremely valuable review effort and suggestions for improvement. I also want to thank the readers for their interest in our articles, which is reflected in the increasing number of accesses and PDF downloads. These contributions, together with the generous financial support of the KOALA initiative, sustain the quality of our journal. n a continuous effort to further strengthen our journal, I would like to expand the editorial board: If you are a tenured associate professor or above with a strong publication record, you are welcome to apply to join our editorial board. We are also interested in high-quality proposals for special issues on new topics and trends. In the seventh regular issue, I am very pleased to introduce the following 5 accepted articles: In a collaboration between researchers from Colombia and Spain, Juan-Sebastián González-Sanabria, Cristian Pinto, Jhon Zuñiga, Hugo Ordoñez, and Xiomara Blanco focus on a XGBoost Classifier-Based Model to predict the nature of gender-based violence based on specific socio-demographic and situational features.Muthukumaran N and Vignesh A from India present enhancements of chatbot responses by addressing challenges such as context retention over extended interactions, syntactic ambiguities and bias propagation from training data. They propose an advanced transformer model, the Improved T5 (IT5), to solve these issues.In a collaboration between researchers from Romania and Lithuania, Eugen Valentin Butilă, Mihai Burlacu, Răzvan Gabriel Boboc, and Robertas Damaševičius discuss the findings of a bibliometric analysis of reviews and research articles on the use of VR applications in anthropology between 2010 and 2023.Last but not least, Davut Çulha from Turkiye addresses scalability aspects through a binary tree blockchain of decomposed transactions, which can reduce the computational overhead required to calculate account balances and make the system more efficient.Enjoy Reading!Best regards,Christian Gütl, Managing Editor-in-Chief